From Prop to Mediator The Changing Role of Written Language in Children's Symbolic Repertoires. Occasional Paper No. 32 - Dyson, Anne Haas.; National Center for the Study of Writing and Literacy, Berkeley, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
The development of written language is intertwined with children's experiences with diverse symbolic media. During their second year of life, children begin to use symbolic tools to invest meaning in drawn marks. The evolution of drawing is linked in complex ways to dramatic gesture and speech, sometimes combined in social play. Exploratory play with print and the use of print as a prop within dramatic play are valuable supports for young children's entry into written language. Children first attempt to orchestrate the system during familiar, manageable activities. Two male children from an ongoing study of literacy development among African-American students in an urban school provide an illustration of how early writing is shaped by social activity and how writing can assume greater functional importance. The children began to consider critically the relationship between their pictures and their texts, as they assumed more deliberate control over the kind of information they would include in each medium. Implications for early childhood education include: (1) children need many opportunities to draw, play, dance, and sing; (2) teachers need to help connect print with the liveliness of children's use of other symbolic forms; (3) teachers should talk to children about their efforts to help them reflect upon their processes; (4) educators should be cautious about uncritically applying "writing process" curricula developed for older children; and (5) caution should be used in applying simple functional models of oral language in research on written language growth. (Four figures of children's drawings are included; 48 references are attached.) (RS)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: R117G10036.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Black Students; Classroom Research; Developmental Stages; Early Childhood Education; Emergent Literacy; Freehand Drawing; Interpersonal Relationship; Social Influences; Writing Research; Written Language; Young Children; Childrens Writing; African Americans; Reports, Research